Membangun Kesadaran Spritual melalui Konseling Berbasis Surau dalam Pengembangan Pariwisata - Irman Irman; Murisal Murisal; Fadhillah Syafwar; Silvianetri Silvianetri; Zubaidah Zubaidah; Putri Yeni (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This research aims to build spiritual awareness through surau-based counseling. Spiritual awareness is a supporting factor for tourism in the Minang realm, because the community adheres to the customary philosophy of sarak jointed, sarak jointed Kitabullah. The target of service is the young generation and mothers in Nagari Pariangan, Tanah Datar District, West Sumatra. The dedication method uses the Parcipatory Action Reserach technique. The results of the dedication found that surau-based counseling was able to foster spiritual awareness of the younger generation and mothers, the birth of a commitment to make spiritual values as a force in developing tourism, increasing the enthusiasm of young people and mothers to develop tourism based on spiritual values, and the desire to restore the function of the surau as central in building spiritual values.